The Sandwich Generation: Family Responsibility And Individual Well-Being - Aghnia Dian Lestari; Faiz Muhammad Kautsar; Salsa Azzahra Irvanianto; Diny Tri Agustin; Siti Khumayah (Journal of World Science, 2025)
This study aims to determine the impact of the dual role of the sandwich generation on the psychological well-being of individuals entering adulthood in Cirebon City who take care of their parents and fulfill family responsibilities. The main focus is on strategies and efforts to maintain a balance between family responsibilities and personal well-being, in order to achieve a more balanced and harmonious life. This study uses a qualitative method with a phenomenological approach to understand the subjective experience of individuals who enter adulthood of 20-30 years as the sandwich generation in Cirebon City. In-depth interviews were conducted to explore the emotions, expectations, and challenges that individuals face while caring for their parents and siblings, as well as how they manage their personal health while taking on the dual role. The results of this study show that some informants are forced to take on the role of the sandwich generation due to family demands. This study shows that the sandwich generation faces a major challenge in balancing the role of caring for their parents and siblings with personal well-being. Although their responsibilities are different, good communication skills and stress management strategies, such as taking time for yourself, are both very helpful. They hope to create financial stability and a fairer division of responsibilities.